The Effects of Gender Differences in Patients with Depression on Their Emotional Working Memory and Emotional Experience - Li, Mi (Behav Neurol, 2015)
A large amount of research has been conducted on the effects of sex hormones on gender differences in patients with depression, yet research on cognitive differences between male and female patients with depression is insufficient. This study uses emotion pictures to investigate the differences of the emotional working memory ability and emotional experience in male and female patients with depression. Despite identifying that the working memory of patients with depression is impaired, our study found no significant gender differences in emotional working memory. Moreover, the research results revealed that memory effects of mood congruence are produced in both men and women, which may explain why the depression state can be maintained. Furthermore, female patients have more emotional experiences than male patients, which is particularly significant in terms of negative emotional experiences. This result provides cognitive evidence to explain why women suffer from longer terms of depression, are more susceptible to relapse, and can more easily suffer from major depressive disorder in the future.